Comparative in vitro multiplication of some grape (Vitis vinifera) genotypes - DEV, RAHUL; SINGH, S K; SINGH, A K; VERMA, M K (The Indian Journal of Agricultural Sciences, 2015)
The objective of the study was to standardize the protocol for effective and mass multiplication of four wine and juice making grape (Vitis vinifera L.) genotypes, viz. Pusa Navrang, Hybrid 76-1 (Hur Ã— Cardinal), Pearl of Csaba and Julesky Muscat. Culture initiation was undertaken on Murashige and Skoog (MS) medium supplemented with 2.0, 4.0 mg/l benzyl amino purine (BAP) and Kinetin individually and in combination with 0.2 mg/l naphthyl acetic acid (NAA). Explant subcultured on MS medium supplemented with 2.0, 4.0 mg/l indole-3-butyric acid (IBA) singly and in combination with 200 mg/l activated charcoal (AC). The rooted plants (30-day-old) were hardened using rooting medium consisting of coco peat + vermiculite + perlite (2:1:1). Among the different growth regulators tried for highest culture establishment (73.85%), minimum day to axillary bud sprout (9.31) and rooting (16.46%), maximum root length (6.28) with 2.0 mg/l BAP + 0.2 mg/l NAA treatment. Highest culture establishment recorded in the genotype Pusa Navrang (45.34%) followed by in Julesky Muscat (44%). Multiplication rate per 5 subcultures was recorded the maximum in Pusa Navrang (5.6) followed by Pearl of Csaba (5.1), and Hybrid 76-1 (4.9). In the present investigation, the application of MS medium containing growth regulators BAP (2 mg/l) + NAA (0.2 mg/l) and IBA (2 mg/l) + AC (200 mg/l) found best for culture initiation and rapid multiplication, respectively. For hardening using glass jar with polypropylene (PP) cap was a better strategy.